Pengaruh Self Efficacy Dan Dukungan Keluarga Terhadap Minat Berwirausaha - Dian Indra Maulida Dian; Rendra Gumilar; Kurniawan (JOURNAL SAINS STUDENT RESEARCH, 2023)
The problem of this research is regarding self efficacy and family support for interest in entrepreneurship. The reaserch method used is a survey method with a quantitative approach. The population in this study were all students of Serba Baktio Suryalaya Senior High School, totaling 465 students. The sampling technique was simle random sampling so that a total of 82 samples were obtained. The data collection technique in this study was using questionnaires and data analysis techniques using the normality test, linearity test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, test the coefficient of determination R2, t test and F test. The results showed that 1) there is a positive and significant effect of self efficacy on interest in entrepreneurship with a significance value (0,000<0,05). 2) there is a positive and significant in family support on interest in entrepreneurship with a significance value (0,006<0,05). 3) there is a positive and significant influence of self efficacy and family support on interest in entrepreneurship with a significance value (0,000<0,05). In the calculation results of the coefficient of determination test, an r square value of 0.247 was obtained, and based on these calculations it can be seen that self-efficacy and family support on interest in entrepreneurship have an influence of 24.7%.